DEVELOPMENT OF EARLY CHILDREN'S TEACHING MATERIALS IN CHILDREN'S INTEREST IN JAMBI PROVINCE - Surti Kanti; Burhanuddin Tolla; Yufiarti Yufiarti (Sriwijaya University Learning and Education International Conference, 2018)
This study aims to develop teaching materials, tribal children in (SAD), Kubu Tribe in Jambi. This instructional material intended for Early Childhood Education (PAUD) Teachers and Tribe children inside. Meanwhile, research and development products produce teaching materials in the form of certified media. Teaching materials or learning print media, containing learning material intended for early childhood tribes in children. The research methodology used in developing teaching materials uses the development model of Dick and Carey system design learning which contains 10 steps of development. Teaching materials for children in the tribe, containing learning material applied through the approach of playing in the natural environment around the tribe with the peculiarities of the inner child tribe. A formative evaluation carried out on the research and development of the product of this teaching material before it tried out to the users, firstly reviewed by experts on the subject matter of Early Childhood Education, Learning Design Experts and Learning Media Experts. Then after this teaching material reviewed, it then implemented or tested for users, especially PAUD Teachers in applying learning materials to children in Jambi Bungku Village. This research and development carried out until the Formative evaluation stage. The results of research and development of teaching materials stated that the material for the early childhood children in Jambi included in the excellent category.